Periodontal Status in Periodontitis Patients with Type 2 Diabetes Mellitus at Tiga Dolok Health Center - Amalia, Martina; Siagian, Jesika Gihon Aprelia; Aritonang, Okie Anggie Jelita (TALENTA Publisher, Universitas Sumatera Utara, 2025)
Background: Periodontitis is an inflammation of the periodontal tissue characterized by loss of attachment and the formation of periodontal pockets. Periodontitis impairs the metabolic control of patients with diabetes mellitus by increasing inflammation and insulin resistance, according to researchers. This study aims to determine the periodontal status and level of gingival inflammation in patients with periodontitis and type 2 diabetes mellitus at the Tiga Dolok Health Center. Method: This research is a descriptive study with a cross-sectional research design. The study's population and sample are patients with type 2 diabetes mellitus accompanied by periodontitis who visit the Tiga Dolok Health Center and meet the established inclusion and exclusion criteria, with a total sample size of 42 samples taken. Results: The research findings indicate that the average pocket depth is 4.052 mm, the average clinical attachment loss is 5.200 mm, and the level of gingival inflammation based on the gingival index shows that 18 individuals (42.9%) fall into the mild category and 24 individuals (57.1%) fall into the moderate category. Additionally, the papillary bleeding index shows that 31 individuals (73.8%) are in the >1 category, and 11 individuals (26.2%) are in the ≤1 category. Conclusion: As you can see, the periodontal health is moderate. The pocket depth is 4.052 ± 0.402 mm, the clinical attachment loss is 5.200 ± 0.822 mm, and the gingival index shows moderate gingival inflammation. In contrast, the papillary bleeding index falls into the category of >1.